2014
DOI: 10.1590/1413-78522014220500978
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the expression of vegf and survival in osteosarcoma

Abstract: Objective: To present a series of 50 consecutive patients with non-metastatic extremity osteosarcoma, and attempt to correlate expression of the vascular endothelial growth factor (VEGF) protein in biopsy tissue to their prognosis regarding overall survival, disease-free survival and local recurrence. Methods: Fifty cases of non-metastatic osteosarcoma of the extremities treated between 1986 and 2006 at Instituto de Ortopedia e Traumatologia da Universidade de São Paulo, São Paulo, Brasil, were evaluated regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…For example, study of VEGF secretion using mice models have suggested a strong relationship between VEGF and tumor aggressiveness [ 65 ]. In addition, two independent studies compared VEGF secretion and non-metastatic osteosarcoma proliferation by clinical observation on patients, and suggested that poor prognosis and high local recurrences can be associated with boosted VEGF secretion [ 86 , 87 ]. The approach developed in this study can also help to systematically analyze the autocrine activities of cytokines in tumors by replicating the conditions which lead to malignancy in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…For example, study of VEGF secretion using mice models have suggested a strong relationship between VEGF and tumor aggressiveness [ 65 ]. In addition, two independent studies compared VEGF secretion and non-metastatic osteosarcoma proliferation by clinical observation on patients, and suggested that poor prognosis and high local recurrences can be associated with boosted VEGF secretion [ 86 , 87 ]. The approach developed in this study can also help to systematically analyze the autocrine activities of cytokines in tumors by replicating the conditions which lead to malignancy in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Advanced Os is considered incurable and has a very poor response to conventional cytotoxic chemotherapy, which is mainly based on methotrexate and doxorubicin [17]. Better understanding of the biology of Os might support the design of new therapeutic strategies, including anti-angiogenic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…After assessing the entire text of the remaining 32 studies, 10 articles were excluded for insufficient data. Finally, 22 studies with a total of 1144 osteosarcoma patients were included in this study [ 10 , 11 , 18 37 ]. The detailed flowchart of the study filtrating process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To clarify the mechanism of VEGF in the advancement of osteosarcoma, the association between VEGF and prognosis features of osteosarcoma has been assessed. However, the prognostic and clinicopathological value of VEGF remains controversial [ 10 , 11 ]. Previous relevant meta-analyses have been performed to define the clinical significance of VEGF expression in osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%